A Comparative Evaluation of Insulin Syringe and Prefilled Pen Usability and Preference among the Population with Diabetes in Pakistan - Abbas, Sameen; Javed, Areej; Khalid, Mamoona; Talha, Syed Muhammad; Zainab, Pakeeza; Bibi, Anum; Bibi, Sidra; Yaseen, Aliza (Journal of Diabetes and Endocrine Practice, 2025)
Diabetes management often requires insulin administration, and the choice of delivery method—vials/syringes or prefilled pens—significantly impacts patient adherence, satisfaction, and outcomes. While prefilled pens offer convenience and ease of use, their higher cost may limit accessibility in resource-constrained settings like Pakistan. This study evaluates the usability and patient preferences for these devices in PakistanA cross-sectional observational study was conducted at the Federal Government Polyclinic Hospital Islamabad, from February 2024 to June 2024. The data were collected from the medical ward, orthopaedic ward, intensive care unit (ICU), medical ICU, and urology ward. A self-structured validated questionnaire was used to collect the demographics and knowledge assessment about the usability and preference of using an insulin pen or vial and syringe (VaS) system. Filled questionnaires were analyzed through SPSS version 26. A p-value ≤0.05 was considered significant.The study found that patients preferred insulin pens for their ease of use, convenience, and reduced risk of pain. Safety concerns, such as pain and bruising at injection sites, were reported less frequently with pens. However, traditional VaS system remained more widely used due to their affordability and accessibility. Patients expressed a willingness to switch to pens if cost barriers were addressed, highlighting the significant role of economic factors in influencing device choice.This study highlights important insights into the usability and patient preferences for insulin delivery methods among diabetic patients in Pakistan. Prefilled insulin pens were generally favored for their ease of use, convenience, and potential to improve adherence, while traditional syringes were more commonly used due to affordability and accessibility. Addressing economic and systemic barriers through policy interventions, cost reduction strategies, and patient education results in optimized diabetes management.
Keywords: diabetes; insulin; prefilled pens; syringes; preference; Islamabad